FAKTOR-FAKTOR PENYEBAB GUGATAN CERAI DI KUA KECAMATAN JOMBANG CILEGON - Azila Salim; Syahra Nur Fauziah; Hunainah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the factors causing divorce lawsuits (cerai gugat) recorded at the Office of Religious Affairs (KUA) of Jombang District, Cilegon City. The increasing number of divorce lawsuits in industrial areas such as Cilegon is a phenomenon worth examining scientifically. This research employs a descriptive qualitative approach with data collection through in-depth interviews, observation, and documentation study at KUA Jombang District. Informants consisted of KUA officers, former wives who filed for divorce, and community figures. The results show that the main factors causing divorce lawsuits at KUA Jombang District include: (1) economic factors such as unstable income and income disparity; (2) disharmony and poor communication between spouses; (3) the presence of a third party or infidelity; (4) domestic violence (KDRT); and (5) lack of religious understanding and weak marriage values. The social conditions of Cilegon City as an industrial area also influence divorce patterns, where modernization and women’s economic independence encourage the courage to file for divorce. This study recommends strengthening premarital guidance and marriage mediation programs at KUA as preventive measures.